PERENCANAAN DAN KELAYAKAN INVESTASI PERKEBUNAN DURIAN DI KECAMATAN LEMBANG, KABUPATEN PINRANG - Ahmad Bahjat; Mais Ilsan; Nurliani Nurliani (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2022)
The goals of this research are as follows: 1. to assess the potential for durian commodity development in Lembang District, Pinrang Regency based on the base commodity 2. to conduct a comparative advantage analysis of the durian commodity in Lembang District, Pinrang Regency 3. to assess the financial and non-financial feasibility of establishing durian plantations in Lembang District, Pinrang Regency. This study was carried out in Lembang District, Pinrang Regency. This study lasted approximately four months, from January to April 2020. The data was analyzed using the investment feasibility method after primary data collection from informants. According to the findings of this study, the yield (LQ) of plant commodities that are the base commodities in Lembang District, Pinrang Regency are durian, orange, and banana. T Based on the results (RDC) of the leading plant commodities in Lembang District, Pinrang Regency, namely durian and banana plants. The financial feasibility of investing in durian plantation planning demonstrates that the investment in planning and the feasibility of durian plantation investment are both feasible. This is demonstrated by the investment criteria's Net Present Value (NPV) of Rp 524,992,410,848, -, the resulting Internal Rate of Return (IRR) of 42.64 percent, Net B/C of 4,65, and Payback Period of 8 years 5 months.